Seed dispersal by bats (Chiroptera: Phyllostomidae) and mutualistic networks in a landscape dominated by cocoa in the Brazilian amazon - Zeneide Damião da Silva; Ely Simone Cajueiro Gurgel; Letícia Lima Correia; Thiago Bernardi Vieira (Global Ecology and Conservation)
Bats play essential roles in neotropical ecosystems, performing crucial ecological functions such as insect pest control, pollination of plants with significant economic, social, and ecological value, and seed dispersal, including that of pioneer plant species. These animals are directly linked to human well-being, and declines in their populations can even have adverse effects, such as increasing the need for pesticides in regions where natural insect control is reduced. The seed dispersal conducted by bats is fundamental for maintaining neotropical biodiversity, as it supports habitat regeneration and the propagation of various plant species. Moreover, the role of these dispersers is enhanced due to their ability to inhabit a variety of environments, from natural forests to anthropized areas. However, the conversion of natural forests into agricultural production areas, as well as urbanization, has affected the structure of mutualistic networks between bats and plants. In this context, the objective of this study was to identify the pattern of seed dispersal by bats of the Phyllostomidae family in an anthropized landscape of the Brazilian Amazon. Data collection was conducted in different areas of natural forest, cocoa cultivation, and urban areas in the municipalities of the States of Pará. Regarding the results, the most representative subfamilies of bats were Carollinae (72.15 %) and Stenodermatinae (21.8 %). The botanical families Piperaceae (35.52 %) and Solanaceae (19.71 %) were the ones most preferred by the bats. Regarding species richness, the general bat-plant interaction network included 15 botanical families and 26 species of bats. The general interaction network was nested (WNODF= 29.8), with low Specialization (H2=0.27), Connectance (0.17), and Modularity corresponding to M=0.21. Thus, we highlight the importance of these species for the restoration of degraded environments. Therefore, through the execution of projects that demonstrate the importance of chiropterochory in the restoration of degraded ecosystems in the Amazon, it will be possible to create measures and subsidies focused on the conservation of bat and plant species that play a role in maintaining the planet's biodiversity.